2011
DOI: 10.7150/ijms.8.397
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills Training For Emergency Nurses

Abstract: Objective: To determine the effects of a communication skills training program on emergency nurses and patient satisfaction.Methods: Sixteen emergency nurses attended a 6-week psychoeducation program that was intended to improve their communication skills. The first 3 sessions of the psychoeducation program consisted of theoretical education on empathy and communication. Other sessions covered awareness, active communication, and empathic skills on a cognitive behavioral basis using discussion, role play, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 14 publications
0
25
0
2
Order By: Relevance
“…Young age also showed an inverse relationship with perceived quality ( Oflaz & Vural, 2010 ; Raper, Davis, & Scott, 1999 ). Other studies showed that information provided by ED nurses and their attention to patient care were positive predictors of high overall satisfaction ( Parra Hidalgo et al, 2012 ; Ak et al, 2011 ; Davis & Duffy, 1999 ).…”
Section: Introductionmentioning
confidence: 97%
“…Young age also showed an inverse relationship with perceived quality ( Oflaz & Vural, 2010 ; Raper, Davis, & Scott, 1999 ). Other studies showed that information provided by ED nurses and their attention to patient care were positive predictors of high overall satisfaction ( Parra Hidalgo et al, 2012 ; Ak et al, 2011 ; Davis & Duffy, 1999 ).…”
Section: Introductionmentioning
confidence: 97%
“…Every health care workers dealing with emergency patient and wounded person to have sufficient hard ware in communication is as important as emergency response (9). In the study that Włoszczak-Szubzda et al made to determine professional communication sufficiency of emergency medical technicians, it is stated that level of students taking specific communication skills education is better, rather than general psychology and general communication skills education (14).…”
Section: Discussionmentioning
confidence: 99%
“…Psycho-education is defined as programs that targeting the process of planned intended development and change therefore using related education, methods and techniques on patients, patient's family or healthy individuals (8). This program can also be used for the same purposes for health care workers except patient or consultant (9)(10)(11).…”
Section: Mersin Vd: Psiko-eğitimin Etkisimentioning
confidence: 99%
“…In line with the results of this study, a study indicated that lack of motivation and tendency, hopelessness, and disinterest of the trainer in his/her own professions were some of the important communication barriers to health education (12). In a study, it was reported that lack of communication and informational skills of trainers played a significant role in impeding their communication with patients (27). Also, the cultural status of the service providers should not be disregarded (26).…”
Section: Discussionmentioning
confidence: 99%